(untitled) - Mowforth, Martin (New York, 2009)
Ch. 1. Introduction; Ch. 2. Globalisation, sustainability, development ; Ch. 3. Power and tourism ; Ch. 4. Tourism and sustainability ; Ch. 5. A new class of tourist: trendies on the trail ; Ch. 6. Socio-environmental organisations: where shall we save next? ; Ch. 7. The industry: lies, damned lies and sustainability ; Ch. 8. 'Hosts' and destinations: for what we are about to receive ... ; Ch. 9. Cities and tourism: guess who's coming to town? ; Ch. 10. Governance, governments and tourism: selling the Third World ; Ch. 11. New tourism and the poor: making poverty history? ; Ch. 12. Conclusion ; App. 1. Travel and tourism-related websites ; App. 2. Websites relating to carbon budgets and carbon offsetting
Keywords: Du lịch,Phát triển bền vững,Tourism,Sustainable development; Nước đang phát triển,Nước đang phát triển,Developing countries,Developing countries